2021
DOI: 10.33774/chemrxiv-2021-s9fhf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A 47-year-old misunderstanding: Indomethacin Polymorph δ revealed to be two plastically bendable crystal forms by 3D electron diffraction

Abstract: Indomethacin is a clinically classical non-steroidal anti-inflammatory drug that has been marketed since 1965. The third polymorph, Form δ, was discovered by both melt and solution crystallization in 1974. δ-indomethacin cannot be cultivated as a large single crystal suitable for X-ray crystallography and, therefore, its crystal structure has not yet been determined. Here, we report the structure elucidation of δ-indomethacin by 3D electron diffraction and reveal the truth that melt-crystallized and solution-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Finally, although more in-depth stability analyses are needed, the results obtained from the present dissolution studies suggest that δ-indomethacin is very soluble compared with other polymorphs and therefore appears particularly suitable for use in immediate-release formulations. Whilst this paper was under review, a second independent structure determination of δ-IMC by 3D ED was reported in a preprint draft focused on polymorphic plasticity and melt crystallization (Lightowler et al, 2021). The availability of 3D electron diffraction, a new and efficient method for structure characterization of poorly crystalline polymorphic forms, appears therefore more and more important for assessing the energy landscape of API's, predicting their real potential for medicinal applications and possibly designing more efficient administration strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although more in-depth stability analyses are needed, the results obtained from the present dissolution studies suggest that δ-indomethacin is very soluble compared with other polymorphs and therefore appears particularly suitable for use in immediate-release formulations. Whilst this paper was under review, a second independent structure determination of δ-IMC by 3D ED was reported in a preprint draft focused on polymorphic plasticity and melt crystallization (Lightowler et al, 2021). The availability of 3D electron diffraction, a new and efficient method for structure characterization of poorly crystalline polymorphic forms, appears therefore more and more important for assessing the energy landscape of API's, predicting their real potential for medicinal applications and possibly designing more efficient administration strategies.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques have proven successful for structure characterization of many polycrystalline materials that are typically out-of-reach for X-ray diffraction methods owing to small crystal sizes, radiation sensitivity or the presence of multiple phases. These include zeolites (Jiang et al, 2011;Willhammar et al, 2014;Guo et al, 2015;Luo et al, 2023), metal-organic frameworks and covalent organic frameworks (Feyand et al, 2012;Zhang et al, 2013;Wang et al, 2018;Huang et al, 2021), proteins and polypeptides (Shi et al, 2013;Sawaya et al, 2016;Xu et al, 2019;Clabbers et al, 2021), pharmaceuticals (Bra ´zda et al, 2019;Gruene et al, 2018;Jones et al, 2018;Clabbers & Xu, 2020;Lightowler et al, 2022), and so forth .…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, nano-crystalline materials do not provide sufficiently high resolution diffraction data, whether due to poor crystallinity or radiation damage during data collection. In these situations, direct-space global optimization methods, typically simulated annealing (SA), are employed (Andrusenko et al, 2021;Lightowler et al, 2022). SA requires a complete molecule, the position and orientation of which within the unit cell are varied in accordance with the symmetry, until an acceptable agreement between the experimental and calculated diffraction data is reached.…”
Section: Introductionmentioning
confidence: 99%